Individualized instruction and contingency management an application of learning principles to the classroom situation - Huang-Mataragnon, Rita ([Metro Manila] Psychological Association of the Philippines, 1972)
This study describes and evaluates the use of programmed instruction principles in two introductory psychology courses. While experimental class I employed most of the features embraced in programmed courses, experimental class II was subjected to an additional treatment- a mastery-before-proceeding contigency. A comparison made between the two experimental classes and a control class in terms of final departmental examination scores showed superior performance in the part of the former, although the class subjected to the supplementary contingency did not differ significantly from the other expiremental class.
Includes bibliographical references (page 68)
Keywords: Psychology Philippines -- Periodicals